Effectiveness of interventions to promote physical activity and/or decrease sedentary behaviour among rural adults: a systematic review and meta‐analysis. (11th April 2017) - Cleland, V.; Squibb, K.; Stephens, L.; Dalby, J.; Timperio, A.; Winzenberg, T.; Ball, K.; Dollman, J.
Summary: Physical inactivity and overweight and obesity are more prevalent among rural than urban populations. This study aimed to review published evidence of the effectiveness of interventions to increase physical activity (PA) and/or decrease sedentary behaviour (SB) among rural adults and to identify factors associated with effectiveness. Seven electronic databases were searched for controlled trials of a PA or SB intervention. Meta‐analysis was conducted using random effects models and meta‐regression. Thirteen studies were included in the qualitative synthesis ( n  = 4, 848 participants) and 12 in the meta‐analysis ( n  = 4, 820). All studies were interventions to increase PA. Overall, there was no effect on PA (standardized mean difference [SMD] 0.11; 95% confidence interval [CI] −0.04, 0.25) or SB (SMD 0.07; 95% CI −0.33, 0.20). In PA subgroup analyses, studies employing objective outcome measures demonstrated effects in favour of the intervention (SMD 0.65, 95% CI 0.30, 1.00), while those using self‐reported measures did not (SMD 0.00; 95% CI −0.11, 0.10). This review highlights significant gaps in our understanding of how best to promote PA and reduce SB among rural adults. Future studies should use objective measures of PA as study outcomes. The absence of interventions to decrease SB is of concern, with immediate action required to address this large knowledge gap.